Overriding Lithospheric Strength Affects Continental Collisional Mode Selection and Subduction Transference: Implications for the Greater India–Asia Convergent System - Li, Qian; Li, Zhong-Hai; Zhong, Xinyi (Frontiers in Earth Science, 2022)
The India-Asia collision, starting from 55±5 Ma, leads to the formation of Himalaya and Tibetan Plateau with great gravity potential energy and large forces acting on the surrounding blocks. However, the subduction transference/jump does not occur in the southern Indian continental margin or the northern Indian oceanic plate as supposed to happen repeatedly during the preceding Tethys evolution; instead, the continental collision and orogeny continues until present-day. The total amount of convergence during India-Asia collision has been estimated to be ~2900-4000 km and needs to be accommodated by shortening/extrusion of Tibetan plate and/or subduction of Greater Indian plate, which is a challenging issue. In order to study the collision mode selection, deformation partition and continental mass conservation, we integrate the reconstruction-based convergence rate of India-Asia collision into a large-scale thermomechanical numerical model and systematically investigate the effects of overriding Tibetan lithospheric strength and the amount of convergence. The model results indicate that absence of subduction transference during India-Asia collision may be attributed to the strain localization and shortening of the rheologically weak Tibetan plate. In case of India-Asia collision for ~50 Myr with a total convergence of ~2900 km, the model with intermediately weak Tibetan plate could reconcile the general deformation partition and continental mass balance of the Himalayan-Tibetan system. However, the longer period of India-Asia collision for ~55 Myr leads to significant shortening of overriding plate that is not consistent with the Tibetan observations, in which case an oceanic basin may be required for Greater Indian continent.